Computertomography-Based Prediction of Complete Response Following Neoadjuvant Chemoradiotherapy of Locally Advanced Rectal Cancer - Maslova, Marina; Herden, Heinz; Schork, Karin; Turewicz, Michael; Eisenacher, Martin; Schroers, Roland; Baraniskin, Alexander; Mika, Thomas (Frontiers in Oncology, 2021)
Therapeutic strategies for patients harboring locally advanced rectal cancer (LARC) and achieving pathological complete response (pCR) after neoadjuvant radio-chemotherapy (neoCRT) become increasingly investigated. Recent trials challenge the current standard therapy of total mesorectal excision (TME). For some patients, watch-and-wait strategy seems a preferable procedure. The key factor in determining individual treatment strategies following neoCRT is the precise evaluation of tumor responses. Contrast-enhanced computer tomography (ceCT) has proven its ability to discriminate benign and malign lesion in multiple cancers. In this study, we retrospectively analyzed ceCT based density of LARC in 30 patients, undergoing neoCRT followed by TME. We compared pre- and post-neoCRT density of the tumors and correlated the results to the amount of residual vital tumor cells in the resected tissue. Overall, density decreased after neoCRT, with the highest decrease in patients achieving pCR. Densitometry demonstrated a specificity of 88% and sensitivity of 68% in predicting pCR, showing favorable performance compared to MRI (specificity 50%, sensitivity 71%) and rectal endosonographic ultrasound (specificity 60%, sensitivity 94%) in our study population. Thus, we claim ceCT based densitometry a useful additional tool in identifying patients with LARC may benefit from watch-and-wait strategy and suggest further prospective studies.